Mapping the Meridians and Acupoints in Traditional Bhutanese Medicine: A Comparative Analysis with Classical Chinese Acupuncture - Kezang Tshering; Hedi Suanto Tjong (HM Publisher, 2025)
Traditional Bhutanese Medicine (TBM), or gSo-ba Rig-pa (Sowa Rigpa), describes vital energy channels (rtsa) and therapeutic points (gsang mig). Classical Chinese Acupuncture (CCA) features a detailed system of meridians (jing luo) and acupoints (xue wei). While both traditions modulate vital energy, a detailed comparative cartography is lacking. This study aimed to map and compare selected TBM channels and acupoints with potential CCA counterparts. A comprehensive review of Sowa Rigpa texts and Bhutanese traditional medical literature was conducted to characterize principal TBM energy channels and therapeutic points, including those for Serkhap (Golden Needle) therapy. Data for five key TBM channels and twenty associated acupoints (pathways, locations, indications) were compiled. Analogous CCA meridians and acupoints were identified based on topography, anatomical landmarks, and traditional indications. A comparative analysis focused on anatomical correspondence, somatic landmarks, and traditional indications (rLung, mKhris-pa, Bad-kan in TBM vs. Qi, Blood, Zang-Fu in CCA). The mapping characterized distinct TBM channels with unique attributes. Comparative analysis (detailed in a table) revealed significant anatomical overlap for 60% (12 of 20) selected TBM acupoints with CCA acupoints, particularly along Bladder, Gallbladder, and Stomach meridians. Notable divergences occurred in channel trajectories and point energetics. Some TBM points, especially for Serkhap, had unique locations or indications rooted in TBM’s humoral theory. Approximately 30% showed partial overlap, and 10% appeared unique. In conclusion, this comparative mapping provides foundational insights into TBM and CCA channel/acupoint systems. Anatomical convergences suggest shared empirical observations, while Sowa Rigpa’s distinct theories offer a unique lens on somato-energetic relationships.